A review on water leakage detection method in the water distribution network - Al Qahtani, Turki; Yaakob, Mohd Saffuan; Yidris, Noorfaizal; Sulaiman, Shamsuddin; Ahmad, Kamarul Arifin (Penerbit Akademia Baru, 2020)
Leak detection in transmission pipelines is crucially essential for safe operation. Pipeline leak detection systems play a crucial role to minimize the probability of occurrence of leaks and hence their impacts. The distribution pipelines in case of urban water supply need to monitor for contaminants such as microbial growth, internal corrosion of the pipe’s material and other deposits. In addition to the loss of water resources, the contaminant can be infiltrated into the piping system. These contaminants affect not only the quality of the water but also the smoothness of the water pipe flow due to the pressure loss and additional frictions. Therefore, it is essential that this problem be quickly detected and repaired. Today there are many available technologies in the domain of leak detection. This paper will provide you with a fundamental understanding of the operating principles of currently available pipeline leak detection technologies.